Financial liberalization and democracy: the role of reform reversals - Nauro F. Campos; Fabrizio Coricelli (Institute for the Study of Labor (IZA), 2009)
The relationship between economic and political liberalization has received a great deal of attention lately, yet the possibility of a nonlinear relationship and the role of reversals remain largely neglected. Focusing on democratization and financial reform, this paper offers evidence for a U-shaped relationship across countries, over time as well as in a panel setting using a wide range of estimators for various reform measures. We link this non-linear relationship to the notion of partial or captured democracy. We provide as well econometric support showing that even when de facto is modelled as a function of de jure financial liberalization, this non-linearity obtains.
urn:nbn:de:101:1-20090909376
Keywords: C23; D72; O38; P16; 330; Reform reversals; political liberalization; economic liberalization; financial reform; Deregulierung; Liberalismus; Wirtschaftsliberalismus; Kapitalmarktliberalisierung; Politische Reform; Demokratisierung; Transformationsstaaten